STRUKTURASI IDEOLOGI CERPEN GERIMIS YANG SEDERHANA KARYA EKA KURNIAWAN - Rakhman, Arif Kurniar (MIMESIS, 2020)
The short story "Gerimis yang Sederhana" by Eka Kurniawan is an interesting literary work to be studied, through hegemony and structuration approaches. This short story presents a psychological impact (trauma) after the violence that occurred in the Chinese community in 1998, especially for victims of 1998 who chose to stay abroad. In the context of ideology, there are four ideologies in this short story, namely: the ideology of tyranny, humanism, conservatives, and liberalism. Tyrannical and conservative ideologies became the dominant group. The ideology of liberalism becomes ideological negotiation. The ideology of liberalism also reflects the author's ideology. Regarding the application of the structuration theory, Eka Kurniawan responded to the condition of the victims of 1998, who were still traumatized. This condition has an impact on their lack of participation in public spaces. The ideology of liberalism is expected to encourage that. As a result, five years later there was a deputy governor (subsequently governor) who was directly elected by the people to lead Jakarta from the Chinese community. That is, there is an influence between the agent (author) with the structure of society